Preparing the Army for Stability Operations Doctrinal and Interagency Issues - Szayna, Thomas S. (RAND Corporation, 2007)
Much activity is being aimed at revising the approach to planning and implementing Stabilization, Security, Transition, and Reconstruction (SSTR) operations. The changes are meant to ensure a common U.S. strategy rather than a collection of individual departmental and agency efforts and on involving all available government assets in the effort. The authors find that some elements essential to the success of the process are not yet in place.